Esej in esejistični stil v slovenski literaturi devetdesetih let - Bavec, Nataša (Slavistična revija, 2002)
The study is a survey ot the Slovene essay in the 1990's. The methodology is based on the interaction of the theoretical model of the essay with specific, immutalbe generic features and on the analysis of specific non-fiction, reflective pieces of prose, which have been characterized by the Slovene literary criticism and the press as essays. Based on award-winning texts in the category of the Slovene essay and on some other works by notable Slovene literary figures, the study aims at separating essays in the narrow literary-theoretical sense from the texts that belong to other forms of reflective prose, but are written in essayistic style.
Keywords: 1990/2000; esej; literarna teorija; literary theory; Slovene literature; slovenska književnost